The relative age effect in FIFA U-17 World Cup: The role of the playing position and the continent - Isin, A.; Melekoglu, T. (Baltic Journal of Health and Physical Activity, 2020)
Background: The aim of this study was to examine the relative age effect of the countries which attended the 2017 FIFA U-17 World Cup and to research the relative age effect in terms of continents and the players` position.